Exploring the occupational injustices of human trafficking. Issue 3 (3rd July 2019) - George, Emma; Stanley, Mandy
ABSTRACT: Human trafficking is a complex global issue described as modern day slavery, and people who are trafficked can experience severe trauma with long term consequences impacting their health and well-being. Drawing on an occupational perspective, we discuss four case studies from the literature to examine occupational marginalisation, deprivation, imbalance, and alienation. Our analysis shows that across different types of exploitation, in diverse geographical locations, forced occupation and a lack of meaningful occupation, both have a negative impact on health. In addition, we argue that the individual experiences of exploitation reflect collective injustices. Human trafficking is therefore a violation of individual occupational rights, and a social and political issue of occupational injustice. Attention on human trafficking from an occupational perspective appears to have been absent from the occupational science literature.